Домінанти управління власністю на рекреаційні природні ресурси - Burkynskyi, Borys; Martienko, Antonina; Khumarova, Nina; Prokopiuk, Aleksander (Dr. Viktor Koval, 2018)
Introduction. The natural resources national ownership, which basis the formation of state and other forms of ownership, has a complex nature, sometimes its interests do not reflect the interests of every member of society, especially this applies to the system of appropriation in the nature use management. The analysis of various aspects of state property management for natural resources is due to the necessity of its development as a complex, integrated process involving the expansion of horizontal and vertical interactions and relationships. Aim and tasks. The aim of the article is to determine the vectors for improving the system of state management by appropriating natural recreational resources for their effective disposal, alternatives to use, and, also receiving and distributing the proceeds of its ownership. In accordance with the article aim, were set the following tasks: to investigate the trends of rent payments and environmental taxes revenues to the state budget; to analyze revenues to the state budget from the use of natural recreational resources, for example, forest and water polyfunctional resources; to provide suggestions, how to improve the property state management of natural recreational resources. Results. Analyze of positive and negative tendencies towards effective state management, based on the experience of managing property ownership on natural recreational resources in different countries of the world, are identified. The essence of appropriation of natural recreational resources as an economic-ecological category is determined, and includes appropriation of income from natural resources and losses for irrational use of them. The budgetary revenues  from the use of natural production factors are analyzed and their insignificant part of the product manufacturing cost in the areas of activity (forest and water management) is determined, where the basis of the produced goods and services are natural resources. The horizontal management functions dissipation of the same natural recreational resources between different ministries and agencies is identified. Priorities recommendations on the improvement of state natural recreational resources property management are given (inter alia, regulatory framework, forecasting and planning, organization, accounting and control). Conclusions. The analysis of rent payments for the natural resources use and environmental taxes shows that almost the free assignment of income from the use of natural capital to economic entities. Thus, summing up the research it can be concluded that the state policy regarding the use of natural recreational capital should be based on ecosystem and polyfunctional approaches, and the most effective directions for its use in various sectors of the national economy and forms of ownership should be determined by the state.